Histological Alterations in the Testicular Tissue Induced by Sildenafil Overdoses - M. Jarrar, Bashir (Drug Metabolism Letters, 2011)
Twenty adult male rabbits (Oryctolagus cuniculus) received sildenafil (0, 1, 3, 6, 9 mg/kg/day) for 4 weeks to investigate the testicular histological alterations induced by overdoses of this drug. Exposure to overdoses of sildenafil had provoked tubular and interstitial histological alterations. Abnormality in the germinal epithelium of the seminiferous tubules included spermatocytes karyopyknosis, spermatocytes degeneration, desquamation, spermatid giant cells and arrest of spermatogenesis. Additionally, increased Leydig cells cellularity, tubular degeneration, thickening of the interstitium were also observed. The encountered histological findings indicate that chronic exposure to sildenafil overdoses produces significant morphological and histological alterations in the testes which finally might lead to complete arrest of spermatogenesis.
Keywords: phosphodiestrase-5